2001
DOI: 10.1002/path.844
|View full text |Cite
|
Sign up to set email alerts
|

The Ets-1 transcription factor is up-regulated together with MMP 1 and MMP 9 in the stroma of pre-invasive breast cancer

Abstract: The first steps of stroma generation are of pivotal importance for carcinogenesis because at this stage are initiated both angiogenesis, the prerequisite for continuous tumour growth, and the proliferation of stromal fibroblasts. These developments contribute to the onset of tumour invasion by secreting several matrix-degrading proteases. Both angiogenesis and the production of proteases are tightly controlled at several levels; of significant importance is transcription. The Ets-1 transcription factor transac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
103
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 45 publications
12
103
1
1
Order By: Relevance
“…Proteases carry out balanced degradation of extracellular matrix components facilitating tumour invasion (56,(79)(80)(81)(82). In quantitative light cycler analyses we found that media conditioned by DU-145 cells induced in fibroblasts expression of mmp-1 mRNA in contrast to LNCaP and PC-3 conditioned media.…”
Section: Discussionmentioning
confidence: 99%
“…Proteases carry out balanced degradation of extracellular matrix components facilitating tumour invasion (56,(79)(80)(81)(82). In quantitative light cycler analyses we found that media conditioned by DU-145 cells induced in fibroblasts expression of mmp-1 mRNA in contrast to LNCaP and PC-3 conditioned media.…”
Section: Discussionmentioning
confidence: 99%
“…This is suggested by the finding of highly upregulated Ets1 transcripts in stromal tissues surrounding breast carcinoma. 28 In the present study, in addition to primary tumors, we used cell lines of highly enriched malignant epithelial cells. The repressed Ets1 expression in these relatively homogenous cells may represent true molecular change in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The primers were modified by a nonspecific tail for concatamerization, for example, 5 0 -CCC CAA ACC CCA AAC CCC-3 0 and 5 0 -GGG GTT TGG GGT TTG GGG-3 0 . This modification provides a network of generated cDNAs and avoids their displacement 16 resulting in a high specificity of signals. Slides were incubated at 41C 1 h, followed for 2 h at 371C.…”
Section: Tissuementioning
confidence: 99%